5-HTTLPR Polymorphism Modulates Neural Mechanisms of Negative Self-Reflection. (15th April 2013) - Ma, Yina; Li, Bingfeng; Wang, Chenbo; Shi, Zhenhao; Sun, Yun; Sheng, Feng; Zhang, Yifan; Zhang, Wenxia; Rao, Yi; Han, Shihui
Abstract : Cognitive distortion in depression is characterized by enhanced negative thoughts about both environment and oneself. Carriers of a risk allele for depression, that is, the short (s) allele of the serotonin transporter promoter polymorphism (5-HTTLPR), exhibit amygdala hyperresponsiveness to negative environmental stimuli relative to homozygous long variant (l/l). However, the neural correlates of negative self-schema in s allele carriers remain unknown. Using functional MRI, we scanned individuals with s/s or l/l genotype of the 5-HTTLPR during reflection on their own personality traits or a friend's personality traits. We found that relative to l/l carriers, s/s carriers showed stronger distressed feelings and greater activity in the dorsal anterior cingulate (dACC)/dorsal medial prefrontal cortex (dmPFC) and the right anterior insula (AI) during negative self-reflection. The 5-HTTLPR effect on the distressed feelings was mediated by the AI/inferior frontal (IF) activity during negative self-reflection. The dACC/dmPFC activity explained 20% of the variation in harm-avoidance tendency in s/s but not l/l carriers. The genotype effects on distress and brain activity were not observed during reflection on a friend's negative traits. Our findings reveal that 5-HTTLPR polymorphism modulates distressed feelings and brain activities associated with negative self-schema and suggest a potential neurogenetic susceptibility mechanism for depression.